Report to participating governments on the ILO regional seminar and training cours in vocational rehabilitation of the disabled held in Denmark 14 July to 2 August 1969) (ILO, 1969)
International Labour Office. United Nations development programme. Technical assistance sector ILO/TAP/AFR/R. 11. Stencil.